PENERAPAN METODE BERCERITA DALAM MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN INDRAMAYU TAHUN 2024 - Hasanah, Rafikah; Iswandi, Irvan; Mas’ud Arifin, Moh. (Sindoro: Cendikia Pendidikan, 2024)
Speaking skill becomes an important aspect of communication that influences the development of students’ character and creativity. And the storytelling method could be employed to stimulate students’ interest, strengthen their understanding of the content, and build confidence in public speaking. The study aims to analyze the implementation of the storytelling method to improve students’ speaking skills in fifth grade of Islamic Primary Boarding School of Ma'had Al-Zaytun. The researcher uses a descriptive qualitative approach, where data is collected through interviews with teachers and students to gain in-depth understanding of learning process. The results show that most students experienced an increase in interest and ability to speak. Storytelling has proven to be effective in supporting students' personal and moral development, and expanding their knowledge and vocabulary as well. Moreover, storytelling helps students participate more actively during lessons, overcome shyness, and increase their confidence in speaking in front of the class. The researcher concludes that storytelling is an effective strategy to improve students' speaking skills with consideration of the story’s relevance and the use of simple structure organization and easy to understand. Keywords: storytelling method, speaking skill